Do Historical Narratives Create Social Norms? The Case of Syrian Christians and Malabari Jews in Kerala - PUSHKAR REDDY
This article uses case studies of the Syrian Christian and Malabari Jew communities to show that a historical narrative may be viewed as the fundamental premise for the existence of endogamous practices within a religious community. Essentially, the narrative itself has come to be presented as proof that certain practices are justified.